119k views
3 votes
What is the solution to the system of equations below?
x + 3y = 1
-3x - 3y = -15

2 Answers

4 votes

Answer:

Explanation:

x + 3y = 1

-3x - 3y = -15

-2x = -14

x = 7

7 + 3y = 1

3y = -6

y = -2

(7, -2)

User Obi
by
5.2k points
7 votes

Answer:

x =7 , y= -2

Explanation:

x + 3y = 1

-3x - 3y = -15

Add the equations together to eliminate y

x + 3y = 1

-3x - 3y = -15

-------------------------

-2x = -14

Divide by -2

-2x/-2 = -14/-2

x = 7

Now we can find y

x+3y = 1

7 + 3y = 1

Subtract 7 from each side

7+3y-7 = 1-7

3y = -6

Divide by 3

3y/3 = -6/3

y = -2

User Oya Canli
by
5.1k points